تحليل رأي الأستاذ عبد الصمد عن نظرية الأسرة السكينة فستبقول راندا، غاندونج فاجار فانجالو، فارح مرزوقي عمار شعبة الأحوال الأشخصية كلية العلوم الإسلامية جامعة محمدية سورابايا - Pastabikul Randa; Gandhung Fajar Panjalu; Farikh Marzuqi (MAQASID, 2020)
ABSTRACTIslam regulates everything in human life, one of which is the problem of marriage. And in this day and age many of the Muslims fail in fostering a sakinah family, and eventually they separate. While Islam does not like it all, because Islam teaches every Muslim how to choose a partner, so it does not cause damage in the household for those who follow the instructions in Islam. Therefore, Muslims need sakinah family concepts for them to practice in their daily families, so that it does not make them confuse in practicing them easily.            From the background of the problem above, the writer formulates the problems into 3, they are 1) What is the concept of the sakinah family according to Abdul Somad? 2) What are the qualifications for a successful sakinah family? 3) How is it applied into our life?This type of research is quantitative. Data collection methods are obtained through the review of books and videos. While the analysis used is the opinion of Ustadz Abdul SomadAbout the Sakinah Family.Based on the results of the discussion in this thesis that building a sakinah family must begin before marriage and after marriage. As for before marriage, he prepares religious knowledge and enters Islamic communities to rid himself of immorality. As for after marriage, he takes care of his partner's feelings, so that there grows love and affection between the two..